O ciclo de preços das commodities e a sua influência no investimento privado brasileiro no período 2003-2022 - Kubiack, Marco Lima (Universidade do Vale do Rio dos Sinos, 2023)
The beginning of the 2000s was marked by a long period of high commodity prices, as a result many emerging countries, including Brazil, experienced an unprecedented period of constant and sustainable growth, which lasted about of a decade. The present work intends to explain this phenomenon through the impact of this commodity price cycle on Brazilian Private Investment between the years 2003 to 2022. The econometric methodology employed allows extracting the cycle of high commodity prices and evaluate its impact on macroeconomic variables, such as Private Investment. Therefore, an attempt was made to construct a specific index for the Brazilian Commodity Export Basket. It was possible to verify that in a cycle of high prices, private investment is positively impacted, as well as other variables, such as economic activity and inflation, while the exchange rate is negatively impacted. These considerations make it possible to infer the magnitude of these impacts, in addition to the transmission channels of these shocks through the different macroeconomic variables, in addition it allows us to reflect on the degree of dependence of the Brazilian Economy on Commodity Price Cycles.
Keywords: Preço de commodities; Investimento; Brasil; Crescimento econômico; Commodity price; Investment; Brazil; Economic growth; ACCNPQ::Ciências Sociais Aplicadas::Economia